Acid-free Hydrothermal Process for Synthesis of Bioactive Glasses 70SiO2–(30-x)CaO–xZnO (x = 1, 3, 5 mol.%) - Ta Anh Tuan; Elena V. Guseva; Le Hong Phuc; Nguyen Quan Hien; Nguyen Viet Long; Bui Xuan Vuong (Proceedings, 2020)
Bioactive glasses 70SiO2–(30-x)CaO–xZnO (x = 1, 3, 5 mol.%) were prepared by the acid-free hydrothermal method in keeping with green chemical technology. The synthetic glasses were investigated by TG-DSC, BET, XRD, and SEM–EDX methods. All synthetic glasses present mesoporous structures consisting of aggregates of nanoparticles. The bioactivity of synthetic glasses was confirmed through the formation of the hydroxyapatite phase after an in vitro experiment in simulated body fluid (SBF) solution. The effect of Zn addition is shown through the decrease in the bioactivity of synthetic glasses. Additionally, the inductively coupled plasma optical emission spectrometry (ICP-OES) analysis indicates that the Zn ions were released from the glassy networks during in vitro experiments, and they act as Zn(OH)2 suspended precipitation to inhibit the apatite deposition. The in vitro experiment in cell culture matter was performed for SaOS2 and Eahy929 cells. The results confirm the biocompatibility of synthetic glasses and the role of Zn addition in the proliferation of living cells.